Autonomous password generation and setting system with cosmic coding and transfer (COSMOCAT) and cosmic time calibrator (CTC) - Hiroyuki K. M. Tanaka; Elena Cantoni; Giancarlo Cerretto; Alan Duffy; Marko Holma; Shanti Krishnan; László Oláh; Marco Sellone; Sara Steigerwald; Dezső Varga (Scientific Reports)
Abstract As wireless sensor networks (WSNs) with Internet of Things (IoT) devices become increasingly widespread and more complex, the threat of cyber-attacks is also increasing. One of the most common ways WSNs can be hijacked is when passwords/IDs are leaked. If the passwords do not frequently change, it is easier for the system to be compromised. However, many organizations and individuals retain old passwords to avoid the hassle and challenge of continually remembering and managing new passwords. COSMO-PASS is a new technique that combines COSMOCAT and CTC to enable hardware-level protection of the WSN nodes. It removes the inconvenience of having its users create, remember, and change multiple passwords. Based on the test experiments and simulations with a 102-cm2-sized (a smartphone-sized) detector, 6–7-digit passwords are automatically generated and transferred to the sensor node within the time range from 1 s to 1 min, depending on the nodal distance (10–50 cm). Consequently, it is confirmed that automatically generated and frequent password updates are possible with COSMO-PASS, which will effectively protect the data and network. Although applications of COSMO-PASS are limited to a short range, since users do not have to know or physically input the password to their system, the phishing risk is greatly mitigated. It is anticipated that the enhanced security level capabilities of COSMO-PASS can easily be applied to the next generation of secured short-haul wireless sensor networks to achieve the realization of safer and smarter communities.